2004
DOI: 10.2205/2004es000155
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the total electron content in the ionosphere from GPS data recorded during the Hector Mine earthquake of October 16, 1999, California

Abstract: The aim of this paper is to analyze the potential resources of GPS monitoring during the recording of potential earthquake precursors using the Hector Mine earthquake that occurred in California, USA, in October 16, 1999. This event was chosen because at the time of this fairly large earthquake (M=7.1) a dense network of ground-based GPS stations was operating, thus providing a fairly high spatial resolution. This paper offers a detailed analysis of the total electron content (TEC) over a fairly long time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 43 publications
7
44
0
1
Order By: Relevance
“…This brief report confirms the results of Afraimovich et al (2004) and Thomas et al (2012), which demonstrated that before the Hector Mine earthquake, the TEC variations are controlled by geomagnetic activity changes and then they cannot be related to the preparation process of the seismic event. In addition to that, even if an external triggering (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This brief report confirms the results of Afraimovich et al (2004) and Thomas et al (2012), which demonstrated that before the Hector Mine earthquake, the TEC variations are controlled by geomagnetic activity changes and then they cannot be related to the preparation process of the seismic event. In addition to that, even if an external triggering (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…They show that the TEC changes documented by Pulinets et al (2007) are not anomalous but normal variations on global scale, and, therefore, these changes are not related to the localised seismic activity of the Hector Mine area. This paper confirms the results of Afraimovich et al (2004) and Thomas et al (2012). Through the use of geomagnetic indices time series it is shown that the presumed precursor of Pulinets et al (2007) was a normal TEC variation induced by solar-terrestrial interaction.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In particular, showed that a few days before the California's 16 October 1999 Hector Mine earthquake (M 7.1) the variability index was higher than the index during strong (Dst ~ -250 nT) geomagnetic storms. At the same time, analysis of the same 1999 Hector Mine earthquake by Afraimovich et al (2004) showed that the behavior of TEC was rather controlled by the local time and by fairly moderate geomagnetic activity than by the earthquake preparation. TEC time series averaged over the entire network were found to be dominated by diurnal (24 hours) and semidiurnal (12 hours) periods reflecting daily solar activity and lunar tides.…”
Section: Introductionmentioning
confidence: 99%
“…Pulinets (2007) suggested that precursory phenomena of this type could be useful for predicting earthquakes. On the other hand, and in a separate analysis, Afraimovich et al (2004) concluded that TEC variations near the epicenter were controlled by solar and geomagnetic activity that were unrelated to the earthquake. In an investigation of these very different results, we examine TEC time series of long duration from GPS stations near and far from the epicenter of the Hector Mine earthquake, and long before and long after the earthquake.…”
mentioning
confidence: 95%